Nationwide survey on the 2005 Guidelines for the Management of Community-Acquired Adult Pneumonia: Validation of differentiation between bacterial pneumonia and atypical pneumonia - Watanabe, Akira; Goto, Hajime; Kohno, Shigeru; Matsushima, Toshiharu; Abe, Shosaku; Aoki, Nobuki; Shimokata, Kaoru; Mikasa, Keiichi; Niki, Yoshihito (Respiratory investigation, 2012)
The Japanese Respiratory Society Guidelines for the Management of Community-Acquired Pneumonia (CAP) in Adults (JRS 2005) was published as a revision of the Basic Concept for the Management of CAP in Adults (JRS 2000). To evaluate the JRS 2005 criteria for differentiating between disease types and assessing the status of antimicrobial agent use in initial treatment, we conducted a prospective survey. The survey was conducted from July 2006 to March 2007 as a nationwide joint study by 200 institutions. The study subjects included patients aged ≥16 years of age who had CAP, and patients who met the inclusion criteria were consecutively enrolled. Disease type differentiation based on JRS 2005 and JRS 2000 was conducted. Disease type diagnosis was also performed based on test results. The sensitivity and specificity of disease type differentiation were calculated. The antimicrobial agents used in the initial treatment were classified as recommended or non-recommended based on JRS 2005. The validity of non-recommended antimicrobial agent use was investigated. A total of 1875 patients were analyzed. Differentiation of atypical pneumonia using the JRS 2005 criteria had higher sensitivity and lower specificity than differentiation using the JRS 2000 criteria. The antimicrobial agents recommended by JRS 2005 were used as initial treatment in a low number of cases. The efficacy of the recommended antimicrobial agents was similar to that of the non-recommended agents. JRS 2005 is advantageous in terms of reducing the number of items used in disease type differentiation. The recommended antimicrobial agents used for the initial treatment are believed to be appropriate.